Spectral Efficient Asymmetrically Clipped Hybrid FBMC for Visible Light Communication - Kumar, Sanjeev; Singh, Preeti (International Journal of Optics, 2021)
Filter bank multicarrier (FBMC) modulation has shown sufficient potential for wireless communication. A hybrid optical FBMC technique is proposed to improve the spectral efficiency of a visible light communication (VLC) system. In this technique, a hybrid asymmetrically clipped optical offset quadrature amplitude modulation FBMC (HACO-OQAM-FBMC) modulation technique is used. Asymmetrically clipped optical FBMC (ACO-FBMC) is used for odd subcarriers, and pulse amplitude modulation-discrete multitone (PAM-DMT) is used for the even subcarriers. The proposed hybrid scheme uses an intensity modulation/direct detection (IM/DD) channel. It is shown that there is no interference on odd subcarriers using the proposed method and receiver demodulation is similar to that of ACO-FBMC receiver. However, clipping noise of ACO-FBMC falls on PAM-DMT subcarriers, which can be cancelled at receiver processing after estimation. The analytical performance of the proposed technique is compared using parameters, namely, bit error rate (BER), spectral efficiency, computational complexity, and peak to average power ratio (PAPR). It is found that HACO-OQAM-FBMC is more spectral efficient than ACO-FBMC and other OFDM-based techniques.